2022
DOI: 10.1101/2022.12.12.520118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired Barrier Integrity of the Skeletal Muscle Vascular Endothelium Drives Progression of Cancer Cachexia

Abstract: Cancer patients experience cachexia, which is characterized by extensive skeletal muscle wasting that worsens the quality of life and increases mortality. Currently, there are no approved treatments that can effectively counteract cancer cachexia. Vascular endothelial cells (ECs) are essential for maintaining tissue perfusion, nutrient supply, and preventing inappropriate transmigration of immune cells into the tissue. However, little is known about the role of the muscle vasculature in cancer cachexia. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…In fact, a recent study utilizing cachexia-inducing tumor models described weakened vascular functions in atrophying muscles. 37 In skeletal muscle tissue, tumors likely exert an extensive impact that does not merely target myofibers. Finally, gene sets identified in this study contribute significantly to our understanding of potential therapeutic targets for mitigating cancer cachexia and associated muscle wasting.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study utilizing cachexia-inducing tumor models described weakened vascular functions in atrophying muscles. 37 In skeletal muscle tissue, tumors likely exert an extensive impact that does not merely target myofibers. Finally, gene sets identified in this study contribute significantly to our understanding of potential therapeutic targets for mitigating cancer cachexia and associated muscle wasting.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently, the loss of vascular density was observed in skeletal muscle of tumor-bearing mice, which preceded the decline in muscle function and mass. 25 Thus, endothelial cells that line the vessels of distant, non-metastatic organs are ideally situated as first responders to factors extruded from the primary tumor. We are the first to show that malignancy causes a loss of capillary density in the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…EC dysfunction has been repeatedly shown to be associated with increased phenotypes of frailty and sarcopenia [ 61 ]. Moreover, recent findings indicate that skeletal muscle vascular attrition precedes cachexia in a mouse model of pancreatic ductal adenocarcinoma, and is associated with increased vascular leakiness and immune cell infiltration [ 62 ]. In line with muscle EC phenotypes in healthy aging, scRNA-seq revealed that muscles in cachexic mice harbor a unique EC subtype with a gene expression signature indicative of decreased angiogenesis and increased immunoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…In line with muscle EC phenotypes in healthy aging, scRNA-seq revealed that muscles in cachexic mice harbor a unique EC subtype with a gene expression signature indicative of decreased angiogenesis and increased immunoregulation. Additionally, multiple cofactors of the transcriptional coactivator PGC1α were found expressed in this EC subtype, which were functionally validated to be important for maintenance of muscle vascular barrier integrity [ 62 ].…”
Section: Introductionmentioning
confidence: 99%